Clinical presentation and management of atypical hemolytic uremic syndrome in Latin America: a narrative review of the literature - Sepúlveda Palamara, R. A.; Modelli de Andrade, L. G. [UNESP]; Fortunato, R. M.; Gómez, B.; Nieto-Ríos, J. F. (Taylor & Francis, 2024)
Introduction: Comprehensive information about atypical hemolytic uremic syndrome (aHUS) is relatively scarce outside of Europe and North America. This narrative review assembles available published data about the clinical presentation and management of aHUS in Latin America. Areas covered: A search conducted in February 2023 of the MEDLINE (from inception), Embase (from inception), and LILACS/IBECS (1950 to 2023) databases using search terms ‘atypical hemolytic uremic syndrome’ and ‘Latin America’ and their variations retrieved 51 records (full papers and conference abstracts) published in English, Spanish, or Portuguese. After de-duplication, manual screening of titles/abstracts and addition of author-known articles, 25 articles were included of which 17 (68%) are full papers. All articles were published during the years 2013–2022. Articles include cohort studies, a registry analysis, and case reports from Argentina, Brazil, Chile and Columbia. Overall, Latin American patients with aHUS present the classic epidemiological, clinical, and genetic characteristics associated with this condition as described in other world regions. Depending on the country and time of reporting, aHUS in Latin America was treated mainly with plasma therapy and/or eculizumab. Where reported, eculizumab substantially improved aHUS-related outcomes in almost all adult and pediatric patients. Expert opinion: Eculizumab has dramatically altered the natural course of aHUS, improving prognosis and patient outcomes. Addressing economic challenges and investing in healthcare infrastructure will be essential to implement strategies for timely detection and early treatment of aHUS in Latin America.
Keywords: Atypical hemolytic uremic syndrome; complement inhibitors; eculizumab; Latin America; ravulizumab